2018
DOI: 10.3390/e20120989
|View full text |Cite
|
Sign up to set email alerts
|

Complex Behavior of Nano-Scale Tribo-Ceramic Films in Adaptive PVD Coatings under Extreme Tribological Conditions

Abstract: Experimental investigations of nano-scale spatio-temporal effects that occur on the friction surface under extreme tribological stimuli, in combination with thermodynamic modeling of the self-organization process, are presented in this paper. The study was performed on adaptive PVD (physical vapor deposited) coatings represented by the TiAlCrSiYN/TiAlCrN nano-multilayer PVD coating. A detailed analysis of the worn surface was conducted using scanning electron microscopy and energy dispersive spectroscopy (SEM/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…The adaptive of hard thin-film PVD coatings [ 46 ], as well as self-lubricating hard coatings [ 47 ], had been developed more than a decade ago [ 48 ]. The adaptive features progress in time through the permanent regeneration of surface nanoscale tribo-films caused by the interaction of the coating material with the external environment [ 49 ]. This is directly related to the process of self-organization during friction [ 48 ].…”
Section: Adaptive Surface-engineered Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptive of hard thin-film PVD coatings [ 46 ], as well as self-lubricating hard coatings [ 47 ], had been developed more than a decade ago [ 48 ]. The adaptive features progress in time through the permanent regeneration of surface nanoscale tribo-films caused by the interaction of the coating material with the external environment [ 49 ]. This is directly related to the process of self-organization during friction [ 48 ].…”
Section: Adaptive Surface-engineered Systemsmentioning
confidence: 99%
“…Such structures determine the adaptive behavior of the studied complex adaptive tribo-system. During friction, these tribo-films are produced on the base surface of the engineered material through structural modification and interaction with the environment (mostly with surrounding oxygen, Figure 1 ) [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Adaptive Surface-engineered Systemsmentioning
confidence: 99%
“…Those run-in results are achieved due to formation of the relevant secondary structures. However, on the initial run-in stage when the equilibrium oxide films are destructed, the coefficient of friction, wear rate, seizure area, temperature in the contact, and thermal conductivity of the surface layers increase [36]. On the initial run-in stage, the following conditions are observed:…”
Section: Introductionmentioning
confidence: 99%
“…In [36] it is shown that the compositions of the secondary structures formed on the initial run-in stage undergo only minor subsequent changes, in spite of changes in sizes and surface layer structures.…”
Section: Introductionmentioning
confidence: 99%
“…During the running-in stage, not only an increase in the contact area and a decrease in the contact load but also the formation of secondary structures occurs. Furthermore, it has been shown [17] that the elemental composition of the SSs was formed at the initial stage of friction.…”
Section: Introductionmentioning
confidence: 99%